The role of interactive multimedia as a problem solving-based learning media for elementary school students - Nyoman Widhi Adnyana (Institute of Computer Science (IOCS), 2023)
In elementary schools the function of interactive multimedia as a learning medium for problem-solving is crucial in helping students comprehend the concepts and principles of problem-solving more thoroughly. Multimedia that is interactive assists students in visualizing how to solve issues, enhances their visual, communication, and creative thinking skills, and makes learning more enjoyable and participatory. A literature study demonstrates that interactive multimedia has the ability to improve students' learning outcomes and assist them in solving problems in a more efficient and effective manner. The value of this study is that educators and developers of learning media must continue to explore innovation and development of interactive multimedia as a learning medium for primary school problem solving.